UTILIZANDO O ENSAIO DE PÓRTICOS PARA A APRENDIZAGEM - Starosky, Priscila Saray; Neumann, Keiti Angélica; Do Nascimento, Angela Andreia Dessbesell Benchimol; Dos Santos, Claudio Da Silva; Valdiero, Antonio Carlos (Salão do Conhecimento, 2014)
Resumo